Experience as a teacher in training from virtuality. - Arias Melo, Arelis (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article aims to make a detailed description of the experience lived through the realization of a pedagogical practice subject to deepen the degree in basic education with an emphasis on mathematics, Spanish language and humanities, said practice was carried out at the Liceo Latinoamericano de Tunja and it performed abnormally since due to the pandemic generated by coronavirus in 2020 and 2021 this year it was developed virtually through encounters on the zoom platform. Having said this, the teacher in training described some successes and failures observed in the different classes, therefore, together with her head teacher, they propose the development of a classroom project that is focused on reinforcing the themes: solar system, planet earth, and their movements. And spatial relationships (cardinal points), said project was carried out in three phases: (first phase: diagnostic, second phase: design and third phase: results / conclusions); for the design of this degree project, the use of multimedia was taken into account as the main didactic strategy for learning these topics. In the same way, the experience lived through the days of said practice is described.